Fenomena Cyber-bullying Dalam Teknologi Media Baru (Instagram) Perspektif Ilmu Komunikasi - Muhammad Irfan (Jurnal Public Relations (J-PR), 2020)
The development of communication technology has developed and has various impacts on the technology and morality of mankind. The Bullying survey conducted by Ditch, Label, recorded that out of 10,000 teenagers, 42 percent of victims of cyber-bullying admitted to getting them on Instagram. In the context of cases of cyberbullying in Indonesia, in Early November 2019, the presenter artist Ruben Onsu made a report to the legal realm against individuals using social media Instagram who insulted their son. The use of the definition of cyber-bullying in the Law can be called law enforcement. Law enforcers tend to consider defamation and cyber-bullying the same offense, even though the two crimes are different in nature. Understanding cyber-bullying requires an understanding of how the media work with a comprehensive understanding of communication science. Understand the difference between cyber-bullying and traditional bullying. This research also explains conceptually cyber-ethics / cyber ethics according to Richard A. Spinello giving a comprehensive meaning about the technology itself with the cyber concepts that cover it. The role of the Government through Kominfo in campaigning for INSAN (Healthy and Safe Internet) is expected to be able to counteract the phenomenon of bullying in Indonesia